DNA nanotechnology: new adventures for an old warhorse - Zakeri, Bijan (Curr Opin Chem Biol, 2015)
As the blueprint of life, the natural exploits of DNA are admirable. However, DNA should not only be viewed within a biological context. It is an elegantly simple yet functionally complex chemical polymer with properties that make it an ideal platform for engineering new nanotechnologies. Rapidly advancing synthesis and sequencing technologies are enabling novel unnatural applications for DNA beyond the realm of genetics. Here we explore the chemical biology of DNA nanotechnology for emerging applications in communication and digital data storage. Early studies of DNA as an alternative to magnetic and optical storage mediums have not only been promising, but have demonstrated the potential of DNA to revolutionize the way we interact with digital data in the future.